Gray Scale Image Hiding Using Wavelet Packet Transform - Jasim, Abbas A. (Iraqi Journal for Electrical and Electronic Engineering, 2009)
This work implying the design of hiding system that hides a gray scale image into another gray scale image using two-dimensional wavelet packet transform. The proposed hiding scheme uses Wavelet Packet Transform (WPT) to embed data elements of the secret image in different frequency bands of the cover image. The data elements of the secrete image are placed within DWT subspaces after simple treatment in order to reduce its significance on the resulting image and to increase security. The resulting image (the cover image within which the secret image is hidden) is called stego_image. Stego_image is closely related to the cover image and does not show any details of the secret image. The proposed system achieves perfect reconstruction of the secret image. All programs in this work is written by MATLAB 7.